COMPARISON OF CARDIORESPIRATORY ENDURANCE AND BODY FLEXIBILITY IN ELDERLY BEFORE AND AFTER TALI RASA YOGA TRAINING IN JEGU VILLAGE, TABANAN - Krisna, Ida Bagus; Wirata, Gede; Sudiman, Jaqueline; Mangku Karmaya, I Nyoman; Nantra, I Ketut (E-Jurnal Medika Udayana, 2025)
Elderly people have a high risk of physical and cognitive impairment. Physical exercise is believed to be a potential solution. One of the recommended physical exercises is yoga. Yoga is a form of physical exercise as well as a culture that has been around for generations. One of the yogas that is part of Balinese culture is Tali Rasa. Several previous studies have described changes that occur in cardiorespiratory endurance and body stiffness after yoga practice. Therefore, researchers are interested in exploring more deeply the influence of Tali Rasa yoga on these two variables as well as preserving and introducing culture to a wider public. The objective of this research is to determine the comparison of cardiorespiratory endurance and body flexibility in the elderly before and after Tali Rasa yoga training in Jegu Village, Tabanan. The research design is a quasi experiment with pre-test and post-test methods. A total of 50 selected elderly people took VO2 max and sit and reach measurements on the first and last days of the study. Followed by the same measurements to find out the comparison of the measurement results. Statistical analysis uses paired t-test. There are differences in the cardiorespiratory endurance and body flexibility in the elderly before and after Tali Rasa yoga training. In cardiorespiratory endurance, changes were found with insignificant results. As well as significant changes in body flexibility.